Urban space as a democratic space: An analysis of the 2022 Pride Parade Media coverage in Belgrade and Sarajevo - Žarković Tatjana; Ždralović Amila; Jocić Nikola (Glasnik Srpskog Geografskog Društva, 2024)
In post-conflict societies internal demarcation is based on tradition, religion, and heterosexual family values and within this frame sexual citizenship is considered “as ideology” and as a threat to society imposed from outside. At the same time the influence and importance of international norms and changes in the standard of international politics and the emerging culture of human rights cause conflict between inside and outside, national sovereignty and universal human rights. This conflict is not specific only to stabilocracy and hybrid systems, but the omnipresent illogicality of a closed system of citizen-ship. Following the Butler’s observation that “conjuncture of street and media constitutes a very contemporary version of the public sphere” (2011: 9), media textual and visual reports about Pride Parade in Belgrade and Sarajevo were analysed. In the analysis focus is on the borders of citizenship within the patriarchal matrix of nation-state confronted with the present bodies on the streets. The analysed textual and visual media reports confirm a hierarchisation of urban public space formed by national history and its material structures.